2016
DOI: 10.1002/pd.4761
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance of fetal lung lesions using the congenital pulmonary airway malformation volume ratio: natural history and outcomes

Abstract: Fetal lung malformations tend to follow one of two distinct growth patterns, characterized by either (1) a maximal CVR between 25 and 26 weeks of gestation or (2) minimal change in relative growth. The mean CVR correlates with postnatal CT size and operative management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 38 publications
2
21
0
3
Order By: Relevance
“…Furthermore, the optimal timing and frequency of CVR assessment have not been extensively studied . Studies on the longitudinal growth pattern of CLLs have suggested that there might be two distinct types of growth patterns in CLLs: one characterized by stable growth and a relative decrease in size throughout gestation and the other, more common, characterized by lesion enlargement, typically from 24 to 29 weeks’ gestation, followed by a substantial reduction in size . We showed that the median CVR before 24 weeks was significantly higher than between 24 and 32 weeks but without a further significant change thereafter.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Furthermore, the optimal timing and frequency of CVR assessment have not been extensively studied . Studies on the longitudinal growth pattern of CLLs have suggested that there might be two distinct types of growth patterns in CLLs: one characterized by stable growth and a relative decrease in size throughout gestation and the other, more common, characterized by lesion enlargement, typically from 24 to 29 weeks’ gestation, followed by a substantial reduction in size . We showed that the median CVR before 24 weeks was significantly higher than between 24 and 32 weeks but without a further significant change thereafter.…”
Section: Discussionmentioning
confidence: 65%
“…There is a variability in published studies with respect to the proposed CVR cutoffs and the criteria used to define neonatal respiratory morbidity . The optimal time to measure the CVR has not been established, taking into consideration the specific growth pattern of these lesions and the fact that the optimal assessment of CVR might not be possible with advancing gestational age . On the other hand, a recent study suggested the ultrasound (US) parameters obtained later in gestation, including the third trimester, might be better predictors of respiratory outcomes in fetuses with CLLs …”
mentioning
confidence: 99%
“…Optou-se por estudar essa relação volumétrica pulmonar em analogia ao CVR ("congenital pulmonar malformation volume ratio"), por esse ser a variável pulmonar mais descrita para a predição dos resultados neonatais em fetos com lesão pulmonar congênita 18,22,96 . Trabalhos na literatura apontam que o CVR é o melhor método preditor das morbimortalidade em fetos com lesão pulmonar congênita quando mensurado próximo a metade da gestação 18,22,96 . No entanto, existe controvérsia para esse poder preditor quando o mesmo é avaliado em idade gestacional tardia 18,22 .…”
Section: Resultados Geraisunclassified
“…Trabalhos na literatura apontam que o CVR é o melhor método preditor das morbimortalidade em fetos com lesão pulmonar congênita quando mensurado próximo a metade da gestação 18,22,96 . No entanto, existe controvérsia para esse poder preditor quando o mesmo é avaliado em idade gestacional tardia 18,22 . Talvez a diferença entre os padrões de crescimento da lesão pulmonar e da circunferência cefálica possam explicar isso 97 23,80,102 , pela reprodutibilidade in vitro 103 e in vivo 78 , por acurácia comprovada em estudos pos mortem 78 , por apresentar maior benefício quando comparado à ressonância magnética (menor custo, maior tolerância e disponibilidade) 78 , por sua reprodutibilidade na avaliação de estruturas irregulares (fato importante para as lesões pulmonares visto que parte das lesões são irregulares e dificultam a mensuração do parênquima pulmonar residual) 81,104 , por avaliar o volume de cada pulmão separadamente 78,89,104,105 e por ser uma técnica validada nos estudos da hipoplasia pulmonar 76-78, 89, 106 .…”
Section: Resultados Geraisunclassified
See 1 more Smart Citation